Multi-Crop Thresher: a low-cost and labour-saving crop threshing/shelling option for smallholder farmers - Matin, M. A.; Mulundu, S.; Zingwari, O. (2025)
The Multi-crop Thresher (MCT) is a low-cost and labour-saving crop threshing/shelling option for smallholder farmers. It can be used to thresh a range of crops such as sorghum, millet, wheat, soybean, cowpea, sugar bean, etc. For a service provider, it is a machine that can generate good income for about 3–4 months in a year when farmers thresh/shell their produce. The diesel engine-powered Multi-crop Thresher is fast compared to manual shelling. It drastically reduces drudgery, labour, time, and cost compared to manual threshing of crops. The thresher has a low cost of operation and maintenance.